Implementation of a piezoresistive MEMS cantilever for nanoscale force measurement in micro/nano robotic applications - Kim, DH; Kim, B; Park, JO (KOREAN SOC MECHANICAL ENGINEERS, 2004)
The nanoscale sensing and manipulation have become a challenging issue in micro/nanorobotic applications. In particular, a feedback sensor-based manipulation is necessary for realizing an efficient and reliable handling of particles under uncertain environment in a micro/nano scale. This paper presents a piezoresistive MEMS cantilever for nanoscale force measurement in microrobotics. A piezoresistive MEMS cantilever enables sensing of gripping and contact forces in nanonewton resolution by measuring changes in the stress-induced electrical resistances. The calibration of a piezoresistive MEMS cantilever is experimentally carried out. In addition, as part of the work on nanomanipulation with a piezoresistive MEMS cantilever, the analysis on the interaction forces between a tip and a material, and the associated manipulation strategies are investigated. Experiments and simulations show that a piezoresistive MEMS cantilever integrated into a microrobotic system can be effectively used in nanoscale force measurements and a sensor-based manipulation.
Keywords: MICROMANIPULATION; NANOROBOTICS; MICROSCOPE